Only wanna be with you : the inside story of Hootie & the Blowfish - Sommer, Timothy (University of South Carolina Press, 2022)
"The inside story of South Carolina's favorite band-- In 1995, Hootie & the Blowfish were at the top of the Billboard charts, playing soldout stadiums, subject of a subplot on FRIENDS. They had a loyal following from a decade of frat shows and touring in the Southeast and Mid-Atlantic, but emerging from the era of grunge, they were far from what the music industry wanted to sell. In Only Wanna Be with You, Tim Sommer--the A&R rep who signed Hootie to Atlantic in 1993--takes readers inside the rise, fall, and rise again of Hootie & the Blowfish. Drawing from extensive interviews with the band, their associates, and music industry insiders, Sommer tells the story of Darius Rucker, Mark Bryan, Dean Felber, and Soni Sonefeld, from their days of dorm room rehearsals to sharing the stage with Bruce Springsteen to Rucker's groundbreaking country career and all of the ups and downs along the road"--